Adsorption/desorption behavior of ciprofloxacin on aged biodegradable plastic PLA under different exposure conditions. Issue 1 (February 2023) - Zheng, Minghao; Wu, Panwang; Li, Liqing; Yu, Fei; Ma, Jie
Abstract: Polylactic acid, one of the degradable plastics, and ciprofloxacin (CIP) are two typical organic pollutants in the water environment. Adsorption of CIP on aged-microplastics may result in their long-range transport and cause compound combination effects. In this study, the sorption of CIP to microplastics in a simulated aging state was examined. The microplastics aged alternately day and night have larger adsorption capacity than those aged continuously. Adsorption isotherms demonstrated that compared to monolayer adsorption of virgin plastic, the adsorption of aged-PLA is more consistent with the Freundlich model, indicating that adsorption is mainly based on multi-molecular layer adsorption on non-homogeneous surfaces. Moreover, the maximum adsorption capacity of continuous aging for CIP was 26.439 mg/g，the maximum adsorption capacity of alternate aging for CIP was 46.913 mg/g. The results of desorption experiments show that the sorption-desorption process of CIP on PLA is irreversible, and the aged have higher desorption capacity, which indicates that aged microplastics are helpful in enriching and fix CIP for a long time. Our results showed that commonly observed PLA can be a carrier of antibiotics in the aquatic environment. Highlights: The adsorption process of CIP on aged MPs-PLA was studied. Two different UV radiations are applied to simulate aging process. Alternating radiation simulates the day alternates with night in the natural environment. Effect of factors (aging time, particle size and solid-to-liquid ratio) was also studied. The desorption experiments of CIP on PLA was also studied.